A carbon nanowire-promoted Cu2O/TiO2 nanocomposite for enhanced photoelectrochemical performance. (27th July 2022) - Ahmed, Kassam; Wang, Yuyin; Bai, Yang; Sekar, Karthikeyan; Li, Wei
Abstract : We started with earth abundant materials to design a heterojunction nanocomposite with excellent visible light photoelectrochemical performance and enhanced durability. Abstract : The use of semiconductors as photoelectrochemical electrodes and photocatalysts has been studied extensively over the last few decades; however, it is challenging to design one single material meeting a wide range of requirements for applications such as photostability, wide light absorbance and earth abundance. In this study, we started with earth-abundant materials, namely TiO2, Cu2 O and carbon, to design a nanocomposite with TiO2 nanofibers (NFs) and Cu2 O nanocubes (NCs) connected by carbon nanowires (NWs). The nanocomposite (C/TiO2 /Cu2 O) demonstrated excellent photo(electro)activity under simulated visible light as well as enhanced durability. Morphologies imaged by electron microscopes showed that TiO2 NFs and Cu2 O NCs were well connected, while thin and long carbon NWs were present throughout the samples and connected the NFs and NCs to form a compact composite. Electrochemical analysis revealed that the band alignment between TiO2 and Cu2 O was typical for a type-II heterojunction, which is favourable for the separation of photogenerated charge carriers. Moreover, carbon NWs act as bridges, thus facilitating more efficient charge transfer. Overall, this research showed the design and preparation of a nanostructured composite with improved charge transfer and photostability for solar photoelectrochemical applications.